The Role of Marriage Age in Shaping Fertility and Reproductive Health Patterns - Acharya, Dille Prasad (Journal of Gurubaba, 2025)
Nearly three in five respondents considered 20 years as the ideal age for marriage, indicating a general consensus on early adulthood as the preferred time for marriage. In practice, nearly two in five respondents got married between the ages of 18 and 20 years, showing that actual marriage age closely aligns with societal expectations. About half of the respondents reported that their husbands were above 20 years at the time of marriage, suggesting that most marriages involved adults rather than very young individuals. More than half of the respondents believed that the ideal age for giving birth is above 20 years, reflecting awareness of mature and safer childbearing practices. In the study area, nearly half of the respondents stated that they were above 20 years old when they had their first child, indicating that many followed recommended practices regarding age at first childbirth. Out of the total respondents, more than one third (34 percent) of respondents had their baby at hospital. The study found that nearly seven in ten (69 percent) respondents replied that their couple were using contraceptives. More than two in five (41 percent) of respondents replied that the ideal number of children is considered as three. Seven in ten (70 percent) of respondents had no desire of more children . More than three in ten (31 percent) of respondents replied that the ideal birth spacing between two children is three years.